(untitled) (Nuntius Antiquus, 2009)
In the present work we intend to scrutinize some of Solon’s compositions following one of his key questions: justice. Since it is a wide theme on his compositions, we focused our analysis on what we call “dynamical balance”. To fulfill our goal on this essay, we present some of the author’s biographical data and also what we can set as static and dynamical on his thought. At the end of our path, concealing all the information gathered, we try to outline the dynamicity of balance for Solon.